Automatic Control Model of Power Information System Access Based on Artificial Intelligence Technology. (25th March 2022) - Jiang, De Yong; Zhang, Hong; Kumar, Harish; Naveed, Quadri Noorulhasan; Takhi, Chandan; Jagota, Vishal; Jain, Rituraj
Abstract : Looking at the issues of low efficiency, poor control performance, and difficult access control of the traditional role-based access control model, an artificial intelligence technique-based power information system access control model has been designed. The detector is designed by artificial intelligence technology, combining artificial neural network, and artificial immune algorithm, which provide the basis for checking the access request module. It has been proved that the design model can effectively support the access and modification of legitimate users and prevent illegal users from accessing, and the control accuracy is high. The use of artificial intelligence (AI) in the power sector is now reaching emerging markets, where it may have a critical impact, as clean, cheap, and reliable energy is essential to development. Artificial intelligence can be proven very efficient for resolving the control and decision-making issues in high complex systems.